2015
DOI: 10.1039/c5ra10136k
|View full text |Cite
|
Sign up to set email alerts
|

Novel organic–inorganic hybrids based on T8 and T10 silsesquioxanes: synthesis, cage-rearrangement and properties

Abstract: A simple approach for the synthesis of well-defined macromolecules based on isolated amino- and amido-functionalized octa T8 and deca T10 silsesquioxanes is presented. Here we show how the reorganization of the siloxane cage-like core (cage rearrangement) can be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
5
13
0
Order By: Relevance
“…The obtained products were identified by high-resolution mass spectrometry. Such reactivity confirms the previously described mechanism 27 concerning T 8 → T 10 cage-rearrangement using the CF 3 SO 3 -/H 2 O system (Scheme 3). In the 1 H NMR, the signals at δ = 8.23 and 8.19 ppm can be assigned to two different imine CH=N groups (see Supporting Information, Figure S24).…”
Section: Cage-rearrangementsupporting
confidence: 90%
See 2 more Smart Citations
“…The obtained products were identified by high-resolution mass spectrometry. Such reactivity confirms the previously described mechanism 27 concerning T 8 → T 10 cage-rearrangement using the CF 3 SO 3 -/H 2 O system (Scheme 3). In the 1 H NMR, the signals at δ = 8.23 and 8.19 ppm can be assigned to two different imine CH=N groups (see Supporting Information, Figure S24).…”
Section: Cage-rearrangementsupporting
confidence: 90%
“…The TG-DTA data are collected in Table S15 (see also Supporting Information, Figures S4-S13). 27 The percentage of the residue after thermolysis stays in agreement with the accuracy of 0.2% of the theoretically calculated mass for the formation of silicon dioxide. The most detrimental substituents are nucleophilic groups, such as amines, which aid the breaking of siloxane bonds, particularly at higher temperatures.…”
Section: Thermal Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…Among fully functionalized POSSs such as T 8 , T 10 , or T 12 containing 8, 10, or 12 silicon atoms, respectively, most interest has been focused on cubic spherosilicates (hexahedral octafunctionalized silsesquioxanes, T 8 ). [2][3][4] Their attractiveness derives from the fact that they are highly soluble in common organic solvents making them useful compounds for the construction of numerous well-defined hybrid materials. Such compounds can effectively anchor various reactive substituents, R, to the siloxane core and, in fact, the structural and physicochemical properties as well as the potential applications of the POSSs are directly related to the precisely designed side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen silsesquioxane, so-called HSQ as e-beam resist [50], is a series of inorganic Si-O framework compounds with a cubic cage structure. The cage rearrangement will be performed by reacting with phosphoric acid at the Si-O-Si bridge of cage structure [51]. Alphazan et al reported that polyhedral oligomeric silsesquioxane (POSS) (Figure 8) carrying phosphorus was grafted onto the oxide-passivated silicon surface [52].…”
Section: Dendrimers -Fundamentals and Applicationsmentioning
confidence: 99%